Isolated Intrasellar Pituitary Mucocele - Dayang Corieza Febriany; Jegan Thanabalan; Lizawati @ Rosclaritha Maidom; Suria Hayati Md Pauzi; Mohamed Arif Bin Hameed Sultan (Gazi University, 2023)
Mucous cyst or mucocele are epithelial lined cavities containing mucous that occurs mainly in the frontal and ethmoid sinuses. Intracranial mucocele is a rare occurrence. We are presenting an interesting case of a young lady, presented with fainting spells, syncopal attack, recurrent frontal headache and blurring of vision for at least 2 months prior to presentation to us. CT scan showed shows a hyperdense mass arising from the tuberculum sellae with no foci of calcification within and no erosion of the adjacent bony structures. The intrasellar mucocele was diagnosed following surgery via trans-sphenoidal approach and biopsy with confirmatory histopathology.